Paramagnetism in Bacillus spores: Opportunities for novel biotechnological applications. Issue 4 (15th December 2017) - Xu Zhou, Ke; Ionescu, Adrian; Wan, Eamon; Ho, Yeuk N.; Barnes, Crispin H.W.; Christie, Graham; Wilson, D. Ian
Abstract: Spores of Bacillus megaterium, Bacillus cereus, and Bacillus subtilis were found to exhibit intrinsic paramagnetic properties as a result of the accumulation of manganese ions. All three Bacillus species displayed strong yet distinctive magnetic properties arising from differences in manganese quantity and valency. Manganese ions were found to accumulate both within the spore core as well as being associated with the surface of the spore. Bacillus megaterium spores accumulated up to 1 wt.% manganese (II) within, with a further 0.6 wt.% adsorbed onto the surface. At room temperature, Bacillus spores possess average magnetic susceptibilities in the range of 10 −6 to 10 −5 . Three spore‐related biotechnological applications—magnetic sensing, magnetic separation and metal ion adsorption—were assessed subsequently, with the latter two considered as having the most potential for development. Abstract : Spores of Bacillus megaterium, Bacillus cereus, and Bacillus subtilis were found to exhibit intrinsic paramagnetic properties as a result of the accumulation of manganese ions both within the spore as well as on its surface. All three Bacillus species displayed strong yet distinctive magnetic properties arising from differences in manganese quantity and valency. Three spore‐related biotechnological applications—magnetic sensing, magnetic separation and metal ion adsorption—were assessed, with the latter two considered as having the most potential for development.